Den norske idrettsmodellen - i utakt med tiden? - Rafoss, K.; Tangen, J. O. (Norsk sosiologisk tidsskrift, 2017)
In this paper, we ask whether the Norwegian sports model is out of step with the times and find that the answer is ´yes` as a result of the outdated way sport and politics are considered. There is a cultural narrative about ?The Norwegian Model` that precludes growing trends and changes in the population`s participation in exercise and sport.